Macular Edema as Unusual Presentation of Non-Arteritic Ischemic Optic Neuropathy (NAION) - Marsha Rayfa Pintary; Ari Djatikusumo; Salmarezka Dewiputri; Syntia Nusanti; Mohamad Sidik (International Journal of Retina, 2022)
Introduction: Non-arteritic Ischemic Optic Neuropathy is the most common type of ischemic optic neuropathy. Nearly half of NAION patients presented with 20/30 or better visual acuity. Central vision is often preserved relative to the visual field loss. Macular edema in NAION patient is rare, and its occurrence may confuse to other disease and lead to unnecessary treatment. Case Report: We identified three NAION patients presented with macular edema. The patients' age was above 40 and had diabetes mellitus (DM). Our patients had clinical findings consistent with NAION with poor visual acuity at the early presentation. Optical coherence tomography examination was performed, and all patients had prominent subretinal fluid. Intravitreal anti-VEGF injection was done on our first patient and no treatment was given to our second and third patient. All patients showed a significant improvement of macular edema. Discussion: Macular edema is a rare clinical manifestation that may contribute a visual deterioration in NAION. The incidence of macular edema in NAION patients is difficult to measure since OCT of macula is not routinely performed. In our report, we encountered three cases of NAION complicated by macular edema that underwent a different approach in therapy. Spontaneous regression of subretinal fluid was seen during observation without any treatment given. Our patients achieved a stable visual acuity and visual field defect. This finding is under the literature that spontaneous recovery will be observed during the natural course of acute NAION. Conclusion: Macular edema is an unusual but self-limiting presentation of NAION. Therefore, a comprehensive examination is needed to prevent any unnecessary treatment.